2020
DOI: 10.3389/fimmu.2020.597863
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Anti-Glomerular Basement Membrane Antibodies in 200 Patients With Systemic Lupus Erythematosus With or Without Lupus Nephritis: Results of the GOODLUPUS Study

Abstract: IntroductionAnti-glomerular basement membrane (GBM) antibodies are pathogenic antibodies first detected in renal-limited anti-GBM disease and in Goodpasture disease, the latter characterized by rapidly progressive crescentic glomerulonephritis combined with intra-alveolar hemorrhage. Studies have suggested that anti-GBM antibody positivity may be of interest in lupus nephritis (LN). Moreover, severe anti-GBM vasculitis cases in patients with systemic lupus erythematosus (SLE) have been described in the literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…Studies found that HLA-DRB1 * 1501 has been associated with susceptibility to both anti-GBM disease and SLE [12]. However, in the largest anti-GBM antibody study conducted in patients with and without LN with SLE in Europe, anti-GBM antibodies were not detected in serum from Caucasian patients with SLE, even in cases of renal involvement [13]. Tese may be explained by diferent genetic backgrounds in the population between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that HLA-DRB1 * 1501 has been associated with susceptibility to both anti-GBM disease and SLE [12]. However, in the largest anti-GBM antibody study conducted in patients with and without LN with SLE in Europe, anti-GBM antibodies were not detected in serum from Caucasian patients with SLE, even in cases of renal involvement [13]. Tese may be explained by diferent genetic backgrounds in the population between studies.…”
Section: Discussionmentioning
confidence: 99%
“…In these patients, alveolar haemorrhage was significantly more frequent than in SLE patients without anti-GBM antibodies, and prognosis was worse (103). However, these findings were not confirmed on Caucasian patients (105). If this discrepancy is due to ethnic differences (106) or to the different specificity of the commercial anti GBM assays (49) is still not known.…”
Section: Anti-gbm Antibodies In Systemic Lupus Erythematosusmentioning
confidence: 92%